CALCULATION OF HARMFUL SUBSTANCES ACCUMULATION IN THE CLOSE AIRSPACE OF THE TESTS-ROOM MACHINES IN AN EMERGENCY - G.V. BELUSHKINA; Y.I. BULYGIN; D.V. DEUNDYAK (Advanced Engineering Research)
Improvement of working conditions under the influence of harmful substances on the machine-building enterprises workers is an actual problem. Reliable data on the technological process for correct calculation of ventilation on the test sites of agricultural machines are required. Existing techniques are focused on the integrated (annual) emissions based on approximate specific indicators of emissions, calculated for abstract sources of pollution without taking into account their individual properties and operating modes. The specified technique of forecasting quality condition of the operating space in regular and emergency situations based on the models earlier developed by the authors that describe processes of forming and allocation of emissions from the pollution source is offered.